Open-source, high performance miniature 2-photon microscopy systems for freely behaving animals - Blake A. Madruga; Conor C. Dorian; Long Yang; Megha Sehgal; Alcino J. Silva; Matthew Shtrahman; Daniel Aharoni; Peyman Golshani (Nature Communications)
Abstract Here we describe the UCLA 2P Miniscope, an open-source miniature 2-photon microscope capable of recording calcium dynamics from neurons in deep structures and from dendrites over a 445 µm × 380 µm field of view. The system utilizes two on-board silicon-based photon detectors for approximately 4-fold greater light collection compared to an optical fiber bundle-based approach. The microscope can electronically focus within a 150 µm range at a native working distance of 720 µm. To test the 2P Miniscope, we recorded calcium dynamics from place cells in hippocampus, resolved calcium transients from dendrites in retrosplenial cortex and we recorded dentate granule cell activity at a depth of over 620 µm, through an intact hippocampus during open field behavior. The miniature microscope itself and all supporting equipment are open-source and all files needed for building the scope can be accessed through the Golshani Lab GitHub repository.